Radio-Histological Correlation of Lung Features in Severe COVID-19 Through CT-Scan and Lung Ultrasound Evaluation - Trias-Sabrià, Pere; Dorca Duch, Eduard; Molina-Molina, Maria; Aso, Samantha; Díez-Ferrer, Marta; Marín Muñiz, Alfredo; Bordas-Martínez, Jaume; Sabater, Joan; Luburich, Patricio; del Rio, Belén; Solanich, Xavier; Dorca, Jordi; et al. (Frontiers in Medicine, 2022)
BACKGROUND: Coronavirus disease 2019 (COVID-19) patients can develop severe bilateral pneumonia leading to respiratory failure. Lung histological samples were scarce due to the high risk of contamination during autopsies. We aimed to correlate histological COVID19 features with radiological findings through Lung Ultrasound (LU)-guided postmortem Core Needle Biopsies (CNB) and Computerized Tomography (CT)-scans. METHODOLOGY: We performed an observational prospective study including 30 consecutive severe COVID19 patients. The thorax was divided into twelve explorations regions to correlate LU and CT-scan features. Histological findings were also related to radiological features through CNB biopsies. RESULTS: Mean age was 62.56±13.27 years-old, 96.7% were male. Postmortem LU-CNB were performed in 13 patients. 30 patients were evaluated with both thoracic LU and chest CT-scan, representing a total of 279 thoracic regions explored. The most frequent LU finding was B2-lines (49.1%). The most CT-scan finding was Ground-Glass Opacity (GGO, 29%). Pathological CT-scan findings were commonly observed when B2-lines or C-lines were identified through LU (PPV 87.1%). 25 postmortem echo-guided histological samples were obtained from 12 patients. Histological samples showed diffuse alveolar damage (DAD) (75%) and chronic interstitial inflammation (25%). The observed DAD was heterogeneous, showing multiple evolving patterns of damage, including exudative (33.3%), fibrotic (33.3%) and organizing (8.3%) phases. In those patients with acute or exudative pattern, two lesions were distinguished: classic hyaline membrane; and fibrin “plug” in alveolar space (acute fibrinous organizing pneumonia, AFOP). C-profile was described in 33.3%, and presented histological signs of DAD and lung fibrosis. The predominant findings were collagen deposition (50%) and AFOP (50%). B2-Lines were identified in 66.7%; the presence of hyaline membrane was the predominant finding (37.5%), then organizing pneumonia (12.5%) and fibrosis (37.5%). No A-lines or B1-Lines were observed in these patients. CONCLUSION: LU B2-lines and C-profile are predominantly identified in severe COVID19 patients with respiratory worsening, which correspond to different CT patterns and histological findings of DAD and lung fibrosis.